Pathways of purine metabolism: effects of exercise and training in competitive athletes - Zieliński, Jacek; Kusy, Krzysztof (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The main part of skeletal muscle adenosine-5'-triphosphate (ATP) is restored by inosine monophosphate (IMP) reamination in the purine nucleotide cycle. The intramuscular resources of IMP may be resynthesized via the quick and economical salvage pathway, in which muscle hypoxanthine (Hx) is reconverted to IMP by hypoxanthineguanine phosphoribosyl transferase (HGPRT). IMP is subsequently reutilized in the adenine nucleotide (AdN) pool. Inosine and Hx, which flow out of the skeletal muscle, represent the loss of AdN precursors. In the latter case, full restoration of resting ATP levels depends on a slow and energy-consuming de novo pathway. Plasma Hx and erythrocyte HGPRT are indirect indicators of muscle metabolism, particularly of AdN degradation, that reflect exercise- and training-induced muscle energy status. Results. Our analyses of long-term training cycles in different sports show that plasma Hx concentration and erythrocyte HGPRT activity significantly change inconsecutive training phases. Both high-intensity sprint training and endurance training incorporating high-intensity exercise lead to a decrease in plasma Hx levels and an increase in erythrocyte HGPRT activity. The lowest Hx concentration and the highest HGPRT activity are observed in the competition phase characterised by low-volume and high-intensity training loads. Training cessation in the transition phase brings about a reverse phenomenon: an increase in Hx levels and a decrease in HGPRT activity. Conclusions. Low plasma purine levels indicate that the administered training adapts the athletes to high-intensity exercise (more economical AdN use, limited purine efflux from muscle into the blood). Such an adaptation is of great importance for contemporary elite athletes. Purine metabolites are more sensitive markers of training status and better performance predictors than typical biochemical and physiological indicators (e.g. blood lactate and oxygen uptake) in highly-trained athletes of different specializations and ages. The use of Hx and HGPRT for monitoring and control of the training process is worthy of consideration.
Keywords: adenine nucleotide catabolism; purinemetabolism; hypoxanthine; one-year training cycle; muscleand metabolic indicator; HGPRT